Deep-brain stimulation - Kringelbach, M; Owen, S; Aziz, T (2007)
Deep-brain stimulation (DBS) is a clinical intervention that has provided remarkable therapeutic benefits for otherwise treatment-resistant movement and affective disorders. The resulting direct causal manipulation of both local and distributed brain networks is not only clinically helpful but can also help to provide novel fundamental insights into brain function. In particular, DBS can be used in conjunction with methods such as local field potentials and magnetoencephalography to map the underlying mechanisms of normal and abnormal oscillatory synchronization in the brain. The precise mechanisms of action for DBS remain uncertain but here we present an overview of the clinical efficacy of DBS, its neural mechanisms and potential future applications. © 2007 Future Medicine Ltd.